DNA-PK, ATM and MDR proteins inhibitors in overcoming fludarabine resistance in CLL cells - Svirnovski, A.I.; Serhiyenka, T.F.; Kustanovich, A.M.; Khlebko, P.V.; Fedosenko, V.V.; Taras, I.B.; Bakun, A.V. (Experimental Oncology, 2010)
The aim of this paper is to perform the comparative study of the effects of DNA-dependent protein kinase (DNA-PK) inhibitors vanillin and NU7026, ataxia telangiectasia mutated kinase (ATM)/ ATM and Rad3 related (ATR) kinase inhibitor caffeine and multidrug resistance (MDR) protein modulator cyclosporine A (CsA) on fludarabine resistant and sensitive lymphocytes from chronic lymphocytic leukemia (CLL) patients.